1986
DOI: 10.1126/science.3014663
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Mutants of HTLV-III with Changes in the 3′ Region and Markedly Reduced Cytopathic Effects

Abstract: A variant of human T-lymphotropic virus type III (HTLV-III) is described that replicates but does not kill normal human T cells in vitro. This variant, designated X10-1, was derived from the genome of a cytopathic HTLV-III clone (pHXB2D) by excision of a 200-base pair segment in the 3' region of the virus, spanning the env and 3'-orf genes. Comparable variants with 55 to 109 base pairs deleted exclusively in 3'-orf produced, in contrast, virus that was extremely cytopathic. On the basis of these findings it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(112 citation statements)
references
References 27 publications
4
108
0
Order By: Relevance
“…The most obvious product of the PCR analysis represented nefmRNA. This was surprising in view of the putative role of nef as a factor that negatively regulates viral transcription in some (Fisher et al, 1986;Luciw et al, 1987;Ahmad & Venkatesan, 1988;Cheng-Mayer et al, 1989;Niederman et al, 1989) but not all studies (Kim, 1989b). Using a similar PCR system for detecting spliced HIV-1BaL mRNAs in macrophages (but without conducting a time-course analysis), Robert-Guroff et al (1990) also found a strong nefmRNA signal in macrophages that had been infected with HIV-IBaL for 12 to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious product of the PCR analysis represented nefmRNA. This was surprising in view of the putative role of nef as a factor that negatively regulates viral transcription in some (Fisher et al, 1986;Luciw et al, 1987;Ahmad & Venkatesan, 1988;Cheng-Mayer et al, 1989;Niederman et al, 1989) but not all studies (Kim, 1989b). Using a similar PCR system for detecting spliced HIV-1BaL mRNAs in macrophages (but without conducting a time-course analysis), Robert-Guroff et al (1990) also found a strong nefmRNA signal in macrophages that had been infected with HIV-IBaL for 12 to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…pGG1 contains a functional clone of HIV-1 (HXB2gpt2 in ref. 9). pGA1 was produced by mutagenesis of the codon encoding Gly-2 in the gag gene of pGG1 to a codon-encoding alanine (4).…”
Section: Methodsmentioning
confidence: 99%
“…The cytoplasmic domain of HIV-1 gp41, spanning residues 706 -856, plays various roles in virus replication, infectivity, transmissibility, and cytopathogenicity (5,(12)(13)(14)(15)(16)(17). The C terminus of the cytoplasmic tail may play a role in viral uncoating or penetration of the viral core into host cells (18).…”
mentioning
confidence: 99%